Applying Indigenist Research Methodologies in Health Research: Experiences in the Borderlands - Saunders, Vicki; West, Roianne; Usher, Kim (The Australian Journal of Indigenous Education, 2010)
Abstract For Indigenous scholars in health sciences, finding “ways of doing” research that value Indigenist knowledge is an important consideration. Indigenist research methodology offers a useful alternative to mainstream research approaches that draw upon orthodox Western knowledge systems. However, as Indigenous research approaches have only recently entered the academic discourses of health science, few courses currently exist to support Indigenous students and their supervisors who work in this area. While negotiating Indigenist methodologies is challenging, more Indigenous scholars are recognising the importance of doing so. This paper will outline some of the issues experienced by two Indigenist research students coming to terms with the relevance of an Indigenist research approach to their study, as well of those of their supervisor, the third author of the paper.